2015
DOI: 10.1007/s40336-015-0141-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the rs6971 polymorphism in TSPO for quantification and study design

Abstract: © 2015, Italian Association of Nuclear Medicine and Molecular Imaging.Second-generation translocator protein (TSPO) radioligands were developed to circumvent the technical short comings of 11C-PK11195, the first TSPO targeting tracer. However, in early clinical positron emission tomography (PET) studies they displayed greater inter- and intra-subject variability than was expected given the promising characteristics they showed in preclinical and in vitro studies. A great deal of this variability, although not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 26 publications
(41 reference statements)
0
39
1
Order By: Relevance
“…In this study, the TSPO polymorphism status did not affect the comparisons between the TSPO tracers for arthritis imaging. Previous data obtained in human brain, indicated that all second-generation TSPO tracers, including the two DPA tracers of the present study, showed reduced binding affinity in patients homozygous for this polymorphism compared to the wild type [22]. This was not found for the first-generation TSPO tracer (R) -[ 11 C]PK11195.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…In this study, the TSPO polymorphism status did not affect the comparisons between the TSPO tracers for arthritis imaging. Previous data obtained in human brain, indicated that all second-generation TSPO tracers, including the two DPA tracers of the present study, showed reduced binding affinity in patients homozygous for this polymorphism compared to the wild type [22]. This was not found for the first-generation TSPO tracer (R) -[ 11 C]PK11195.…”
Section: Discussioncontrasting
confidence: 46%
“…The homozygous TSPO polymorphism rs6971 is known to affect the binding affinity of second generation TSPO tracers [22]. For correct interpretation of data the genetic TSPO status of patients was determined.…”
Section: Methodsmentioning
confidence: 99%
“…6,7 [ 11 C]PK11195 gives a poor signal-to-noise ratio, 6 while the use of second-generation TSPO tracers is limited by the single nucleotide polymorphism (rs6971) in the TSPO gene, 8 which affects their binding affinity. 9 All TSPO radiotracers can bind plasma proteins, platelets and monocytes to various extents and such binding can be altered in pathological conditions affecting the peripheral immune system, such as systemic inflammation. [10][11][12][13][14][15] For these tracers, free plasma fractions are generally very low (<5%) and difficult to measure, 7,16 a matter that complicates further the quantification of image data.…”
Section: Introductionmentioning
confidence: 99%
“…One of the limitations of second generation TSPO ligands exacerbating clinical translational hurdles is the existence of an rs6971 polymorphism within the gene encoding for TSPO that affects the binding affinity of TSPO ligands 93 - 97 . This polymorphism results in a non-conservative single amino acid substitution from alanine to threonine at amino acid residue 147 (Ala147Thr) of the TSPO gene causing an inter- and intra-individual variability in binding affinity, hampering quantification of imaging data 98 , while at the same time no effect of Ala147Thr on inflammatory and cerebrovascular biomarkers was observed 99 .…”
Section: Microgliamentioning
confidence: 99%
“…This implicates that the choice of the TSPO ligand, as well as the TSPO status of the individuals included in a study, may severely influence the outcome of the clinical trial. Thus, statistical methods accounting for the TSPO status and matching of patients should be performed 98 .…”
Section: Microgliamentioning
confidence: 99%